Freedom of Contract Versus Public Regulatory Control in Government Construction Contracts: A Legal Analysis Under Law No. 2 Of 2017 on Construction Services - Melkianus Ndaomanu; Frengky Ndaomanu; Dian Nustanti Ndaomanu (Greenation Research & Yayasan Global Resarch National, 2026)
The principle of freedom of contract is a fundamental doctrine in private law that grants parties autonomy to determine agreements. In Indonesian civil law, this principle is reflected in Article 1338 of the Civil Code, which affirms that legally concluded agreements bind the parties. However, its application is more complex in government construction contracts because they involve public resources and public policy. This study analyzes the application and limitations of contractual freedom in government construction agreements under Law No. 2 of 2017 on Construction Services. This research uses a normative juridical approach to examine statutory regulations, legal doctrines, and scholarly perspectives. The findings show that contractual autonomy operates as regulated autonomy rather than absolute freedom. Procurement regulations, administrative authority, technical standards, and public accountability mechanisms significantly influence the structure and implementation of construction agreements. These regulatory constraints produce several legal consequences, including limited negotiability of contractual clauses, potential invalidity of provisions exceeding administrative authority, and stronger requirements for regulatory compliance in determining contractual validity. The study further indicates that these limitations require a more structured approach to drafting government construction contracts, emphasizing standardized clauses, transparent procurement procedures, and clear risk allocation. Strengthening the balance between contractual flexibility and regulatory oversight is therefore essential to improve legal certainty, accountability, and efficiency in public infrastructure development.